THERMAL IMAGES PRE-PROCESSING FOR EARLY DETECTION OF BREAST CANCER: A PROGRESSIVE REVIEW - Azman Brahim Llaguno Garcia; Arturo Orellana Garcia; Vivian Estrada Senti (Acta Informatica Malaysia, 2024)
The aim of this study is to identify the pre-processing stage as a necessary step in the thermal image processing to support the decision-making in health institutions. Digital infrared thermal imaging allows the identification of unrecognized diseases in an apparently healthy population, through a thermal map generated by the temperature of the affected area. The methods used to identify the main aspects that affect the quality of the thermal image were inductive-deductive, historical-logical, analytical-synthetic and document analysis. As a result, the necessary initial conditions for the acquisition and the logical sequence to be develop in the pre-processing stage were presented.